Grain Quality Evaluation of Traditionally Cultivated Rice Varieties of Goa, India - Krishnan Sellappan*, Shilpa J. Bhonsle and (Recent Research in Science and Technology, 2010)
Abstract The physicochemical characteristics such as physical (hulling, head rice recovery (HR), broken rice (BR), grain classification, chalkiness), chemical (alkali spreading value, amylose content (AC), gel consistency (GC), aroma) and cooking characteristics (volume expansion, elongation ratio, water uptake) were studied for 22 traditionally cultivated rice varieties from Goa, in comparison with high yielding rice varieties Jaya, Jyoti and IR8. The hulling percentage ranged from 63-81% and HR recovery from 45-74%. Among the varieties Length/Breath ratio ranged from 1.5-3.5 and the AC ranged from 14-25%. The lowest percentage of chalkiness was recorded in variety Barik Kudi. Highest GC was recorded in variety Salsi and lowest in Khochro.Â The kernel elongation ratio ranged from 4.78-1.83 mm and water uptake ratio ranged from 160-390. Some of traditionally cultivated rice varieties are with excellent grain quality characteristics. The rice variety korgut which predominantly grown in khazan lands could be used in breeding programmes to develop high saline varieties. Keywords: Amylose content, Grain quality, Physicochemical characteristics, Traditional rice varieties